2011
DOI: 10.1083/jcb.201102090
|View full text |Cite
|
Sign up to set email alerts
|

TOR kinase complexes and cell migration

Abstract: Cell migration is a fundamental process in a wide array of biological and pathological responses. It is regulated by complex signal transduction pathways in response to external cues that couple to growth factor and chemokine receptors. In recent years, the target of rapamycin (TOR) kinase, as part of either TOR complex 1 (TORC1) or TOR complex 2 (TORC2), has been shown to be an important signaling component linking external signals to the cytoskeletal machinery in a variety of cell types and organisms. Thus, … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
59
0

Year Published

2011
2011
2018
2018

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 80 publications
(62 citation statements)
references
References 140 publications
(210 reference statements)
3
59
0
Order By: Relevance
“…Recent studies have shown that mTOR also plays a critical role in the regulation of tumor cell motility, invasion, and cancer metastasis (41). However, the role of GOLPH3 in cancer cell migration and metastasis remains largely unknown.…”
Section: Expression Of Golph3 Is Important For Integrin-meditatedmentioning
confidence: 99%
“…Recent studies have shown that mTOR also plays a critical role in the regulation of tumor cell motility, invasion, and cancer metastasis (41). However, the role of GOLPH3 in cancer cell migration and metastasis remains largely unknown.…”
Section: Expression Of Golph3 Is Important For Integrin-meditatedmentioning
confidence: 99%
“…Circulating naive neutrophils are apolar, but upon stimulation by chemoattractants they rapidly polarize in a manner that is epitomized by formation of lamellar-type F actin at the front and localization of active RHOA and phosphorylated myosin light chain (pMLC, also known as MYL2) at the back (Bourne and Weiner, 2002;Graziano and Weiner, 2014;Liu and Parent, 2011;Wang, 2009;Wu, 2005). It remains, however, incompletely understood how RHOA activation and pMLC localization is polarized.…”
Section: Introductionmentioning
confidence: 99%
“…As a serine/threonine protein kinase, mTOR mediates growth factor–induced cell migration 62. mTOR inhibitors were clinically approved to reduce restenosis after angioplasty for patients with vascular occlusion 63, 64.…”
Section: Discussionmentioning
confidence: 99%